ANALISIS KONFLIK TOKOH UTAMA DALAM NOVEL AIR MATA TUHAN KARYA AGUK IRAWAN M.N - Agustina, Rini (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2016)
This study focuses on internal conflicts in the novel Air Mata Tuhan works Aguk Irawan M.N. The method in this article uses descriptive method and form of qualitative research. Psychology humanities is used as an approach in this article. Data collection technique used is the technique of documentary studies to reviewingÂ  creation humanities. Data collection tool used is the Human Instrument with the help of card data recorder. Technique authenticity of data used are, triangulation investigator, theory triangulation and inspection peers through discussion. The analysis technique used is the study of the contents. External conflict contained in the novel Tears God works Aguk Irawan M. N based on the analysis that researchers do, namely social conflict tangible problem accusation, strife, oppression, and opposition. Internal conflicts contained in the novel Tears God works Aguk Irawan M. N based on the analysis that researchers do that is the inner conflict in the form of expectations, and the conflicts between the two desires